Self Nanoemulsifying Drug Delivery System (SNEDDS) Grapeseed Oil Formulation Using Tween 20 And Cremophor Rh40 As Surfactant - Andjani, Nathania Humaira; Wahyudi S, Made Dwi Pradipta; Somatirta, I Gede; Anggraini, Jessica Sanchez (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Grape seeds (Vitis vinivera) oil is not only known to have antioxidant activity, but also known to have solubility and bioavailability problems. One way that can be used to overcome this problem is to formulate it into a Self-Nanoemulsifying Drug Delivery System (SNEDDS). SNEDDS is a system that consists of oil phase and surfactants mixture that will form nanoemulsions when stirred in water. The aim of the study was to optimize the oil phase and surfactant mixture composition, since it has been known to affect the SNEDDS characteristics. SNEDDS grapeseed oil was made with a mixture of surfactant tween 20 and cremophor RH40 which was optimized using the simplex lattice design approach with Design Expert 13.0.10. This study provided that the SNEDDS optimum formula consists of 5.73% grapeseed oil, 10% cremophor RH40, and 84.26% tween 20. The system could be emulsified in 5.32 seconds, with a transmittance of 99.435%, a droplet size of 13.5 nm, a PDI of 0.476, and a zeta potential of -21.0mV. Based on the stability test results, the resulting system was observed to be stable against dilution, freeze thaw, and centrifugation, which make the system acceptable as SNEDDS.